2014
DOI: 10.1002/cbin.10357
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of human tooth germ stem cells into endothelial‐ and epithelial‐like cells

Abstract: Current clinical techniques in dental practice include stem cell and tissue engineering applications. Dental stem cells are promising primary cell source for mainly tooth tissue engineering. Interaction of mesenchymal stem cell with epithelial and endothelial cells is strictly required for an intact tooth morphogenesis. Therefore, it is important to investigate whether human tooth germ stem cells (hTGSCs) derived from wisdom tooth are suitable for endothelial and epithelial cell transformation in dental tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…An interesting phenomenon was that BMSCs showed slight CK10 expression in vitro, but this expression was initially negative in vivo and became positive at 30 d. This finding may be explained as an adaptive process of the cells, which could partially lose their original orientation in vivo and, thus, minimise their expression profile until the epithelium became fully differentiated. These results, related to the in vitro differentiation potential of WJSCs and BMSCs, were in agreement with previous work demonstrating their keratinocytic differentiation capability (Garzon et al, 2013) and with the fact that ADSCs and DPSCs have not yet been differentiated into skin keratinocytes -although reports have suggested that these cell types may have epithelial differentiation capability in the presence of inductive medium (Baer et al, 2013;Dogan et al, 2015). In the present study, both WJSCs and BMSCs were able to develop a larger number of cell layers at the in vitro stage, which coincided with the early cytokeratin expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An interesting phenomenon was that BMSCs showed slight CK10 expression in vitro, but this expression was initially negative in vivo and became positive at 30 d. This finding may be explained as an adaptive process of the cells, which could partially lose their original orientation in vivo and, thus, minimise their expression profile until the epithelium became fully differentiated. These results, related to the in vitro differentiation potential of WJSCs and BMSCs, were in agreement with previous work demonstrating their keratinocytic differentiation capability (Garzon et al, 2013) and with the fact that ADSCs and DPSCs have not yet been differentiated into skin keratinocytes -although reports have suggested that these cell types may have epithelial differentiation capability in the presence of inductive medium (Baer et al, 2013;Dogan et al, 2015). In the present study, both WJSCs and BMSCs were able to develop a larger number of cell layers at the in vitro stage, which coincided with the early cytokeratin expression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to adipocyte, chondrocyte and osteoblast differentiation potential, MSCs have epithelial differentiation capability and heterotypical models of artificial tissues could be generated using MSCs as alternative cell sources (Garzon et al, 2013). In this regard, preliminary reports support the epithelial differentiation capability of ADSCs (Baer et al, 2013) and human tooth-derived stem cells (Dogan et al, 2015). In turn, WJSCs are efficiently differentiated into cornea epithelial cells (Garzon et al, 2014) and human skin as well as oral mucosa keratinocytes (Garzon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the angiogenic potential of stem cells derived from dental pulp, gingival fibroblasts, and tooth germ has been demonstrated, putting in evidence that the oral neural crest derived stem cells may be appropriate for generating endothelial tissues (Dogan, Demirci, & Sahin, ; Iohara et al, ; Szepesi et al, ). In our study, we have induced xeno‐free hPDLSCs to endothelial commitment and their differentiation ability was appraised trough CD31 expression evaluated using multiparametric analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The flow cytometry analysis of cells was completed using a Becton Dickinson FACS Calibur (Becton Dickinson, San Jose, CA) flow cytometry system. Characterized cells were then differentiated into adipo-, chondro-, and osteogenic lineages to confirm mesenchymal stem cell (MSC) properties as described previously [16]. Briefly, cells were seeded on six well plates at a cell density of 5×10 4 cells/well.…”
Section: Isolation and Characterizationmentioning
confidence: 99%